The long-term effects of mandatory military on health outcomes. (30th September 2020) - Cavalli, N; Boccia, S; Giraldi, L; Mariani, M; Ricciardi, W; Nicodemo, C
Abstract: Introduction: In the past many young men spent a period of time in military service. To enter in the military service the person should pass a health visit where the physical and mental health conditions were verified. We focus our analysis on the Italian military service that was stopped to be mandatory in 2004, to explore if health visits during the military service have effects in preventing future illnesses. To do that we compare health outcomes of the cohort of Italian people born in 1985 and in 1987, i.e. before and after the suppression of the mandatory military service, respectively. Methods: Data on demographic characteristics of men potentially enrolling the last compulsory military visit and the one after the abrogation were obtained from the Italian National Statistics Institute. For health outcomes, we obtained for the same population the health records of hospital admissions from 2007 to 2017. A difference-in-difference analysis was performed to calculate whether the probability of being differed among the two cohorts of people. Results: A total of 215, 081 males born in 1985 and 210, 616 males born in 1987 were admitted to hospital in the period 2007-2017. A decreasing trend from 2007 to 2017 in overall hospitalization rates were observed for both cohorts of 1987 (1.26 to 1.15) and 1985 (1.22 to 1.13). The regression model showed a significant lower probability for the 1985 cohort, respect to the 1987, of being admitted for an infectious or parasite disease (coefficient -0.83; 95% CI: -1.15 - -0.51) and for tumours (coefficient = -0.83, 95% CI:-1.57 - -0.09) Conclusions: To our knowledge, this is the first study that attempted to quantify the potential preventive impact in the male population of the physical examination during the mandatory military visit. With an age difference of 2 years between the 2 cohorts, the results show a significant reduction in terms of hospital admission for certain types of health conditions Key messages: The mandatory military service was helpful in detecting certain diseases whose diagnosis would otherwise be delayed or undetected. Physical and mental examinations for mandatory military service, could see how a potential screening programme of prevention among young men.